Transient ischaemic attack: clinical relevance, risk prediction and urgency of secondary prevention. - Giles, M; Rothwell, P (2009)
PURPOSE OF REVIEW: Transient ischaemic attack (TIA) is increasingly recognized as a harbinger of stroke and an important opportunity for secondary prevention. We have reviewed recent evidence on the burden of TIA and prediction and prevention of stroke in the acute phase. RECENT FINDINGS: Although recent data on the incidence and prevalence of TIA are lacking, available data suggest that the burden of TIA is higher than previously estimated and may be expected to increase with the ageing of the population. Prospective prognostic studies have shown that the early risk of stroke after TIA is approximately 5% at 7 days and 10-15% at 90 days depending on clinical settings and study methodology. This risk can be reliably predicted by risk scores based on clinical features (the ABCD system), TIA aetiology and findings on brain imaging, although the optimal combined prognostic strategy is uncertain because the interaction between individual predictors is not established. Studies of the urgent assessment and initiation of secondary prevention in specialist centres suggest that the early risk of stroke after TIA can be reduced by up to 80%. SUMMARY: The risk of stroke after TIA is considerable. However, recent advances have shown that this risk can be predicted for individuals and substantially reduced by appropriate secondary prevention measures.